Answer:
For the function
the average rate change from x is equal 1 to x is equal 2 is 4 .
Step-by-step explanation:
A function is given f(x)=4x-3.
It is required to find the average rate change of the function from x is 1 to x is 2 . simplify.
Step 1 of 2
A function f(x)=4 x-3 is given.
Determine the function
by putting the value of x=1 in the given function.
![$$\begin{aligned}&f(1)=4(1)-3 \\&f(1)=1\end{aligned}$$$$f(1)=1$$](https://tex.z-dn.net/?f=%24%24%5Cbegin%7Baligned%7D%26f%281%29%3D4%281%29-3%20%5C%5C%26f%281%29%3D1%5Cend%7Baligned%7D%24%24%24%24f%281%29%3D1%24%24)
Determine the function
by putting the value of x is 2 in the given function.
![$$\begin{aligned}&f(2)=4(2)-3 \\&f(2)=5\end{aligned}$$](https://tex.z-dn.net/?f=%24%24%5Cbegin%7Baligned%7D%26f%282%29%3D4%282%29-3%20%5C%5C%26f%282%29%3D5%5Cend%7Baligned%7D%24%24)
Step 2 of 2
According to the formula of average rate change of the equation ![$\frac{\Delta y}{\Delta x}=\frac{f\left(x_{2}\right)-f\left(x_{2}\right)}{x_{2}-x_{1}}$](https://tex.z-dn.net/?f=%24%5Cfrac%7B%5CDelta%20y%7D%7B%5CDelta%20x%7D%3D%5Cfrac%7Bf%5Cleft%28x_%7B2%7D%5Cright%29-f%5Cleft%28x_%7B2%7D%5Cright%29%7D%7Bx_%7B2%7D-x_%7B1%7D%7D%24)
Substitute the value of
with,
with
with 2 and
with 1 .
![$$\begin{aligned}&\frac{\Delta y}{\Delta x}=\frac{5-1}{1} \\&\frac{\Delta y}{\Delta x}=4\end{aligned}$$](https://tex.z-dn.net/?f=%24%24%5Cbegin%7Baligned%7D%26%5Cfrac%7B%5CDelta%20y%7D%7B%5CDelta%20x%7D%3D%5Cfrac%7B5-1%7D%7B1%7D%20%5C%5C%26%5Cfrac%7B%5CDelta%20y%7D%7B%5CDelta%20x%7D%3D4%5Cend%7Baligned%7D%24%24)